The neuroprotective effects of melatonin against diabetic neuropathy: A systematic review of non-clinical studies - Hosseini, Asieh; Samadi, Mahedeh; Baeeri, Maryam; Rahimifard, Mahban; Haghi-Aminjan, Hamed (Frontiers in Pharmacology, 2022)
Backgrounds: Diabetes can cause diabetic neuropathy (DN), a nerve injury. High blood sugar (glucose) levels can harm nerves all over your body. The nerves in your legs and feet are the most commonly affected by DN. The purpose of this study was to conduct a review of melatonin’s potential neuroprotective properties against DN. Method: A full systematic search was conducted in several electronic databases (Scopus, PubMed, and Web of Science) up to March 2022 under the PRISMA guidelines. Forty-seven studies were screened using predefined inclusion and exclusion criteria. Finally, the current systematic review included nine publications that met the inclusion criteria. Result: According to in vivo findings, melatonin treatment reduces DN via inhibition of oxidative stress and inflammatory pathways. However, compared to the diabetes groups alone, melatonin treatment exhibited an anti-oxidant trend. According to other research, DN also significantly produces biochemical alterations in neuron cells/tissues. Additionally, histological alterations in neuron tissue following DN were detected. Conclusion: Nonetheless, in the majority of cases, these diabetes-induced biochemical and histological alterations were reversed when melatonin was administered. It is worth noting that the administration of melatonin ameliorates the neuropathy caused by diabetes. Melatonin exerts these neuroprotective effects via various anti-oxidant, anti-inflammatory, and other mechanisms.